Bibliometric Insights in Advances of Anaplastic Thyroid Cancer: Research Landscapes, Turning Points, and Global Trends - Hanyu Wang (Frontiers Media S.A., 2021)
BackgroundThyroid cancers are the most common endocrine malignancies with a dramatic increase in incidences. Anaplastic thyroid cancer is a rare but deadly form among thyroid cancers. To better understand of this field, we assessed the global scientific outputs and tried to depict its overview via bibliometric methods.MethodsApproximately 1,492 science publications published between 1997 and 2020 were included by systematic retrieval in the WoS database. The general information of them was characterized, and the developmental skeleton and research frontiers were explored.ResultsThe article number in this field has been increasing in the past 24 years. North America, East Asia, and Western Europe have reached remarkable achievements. Mutations of BARF and TERT and their downstream pathways have attracted researchers’ attention, where genetic diagnosis provides new clinical insight and several targeted therapeutic approaches have been on the clinical trial.ConclusionsNumerous efforts have been made to figure out gene expression reprogramming of anaplastic thyroid cancer and key mechanism in driving its dedifferentiation, invasion and migration process. Targeted therapy, immunotherapy, and systematic combination therapy are the recent current research hotspots. These results provide insightful clues for the funding direction and the potential breakthrough direction of the anaplastic thyroid cancer study.